2003
DOI: 10.1002/14651858.cd004016
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid injections for shoulder pain

Abstract: Despite many RCTs of corticosteroid injections for shoulder pain, their small sample sizes, variable methodological quality and heterogeneity means that there is little overall evidence to guide treatment. Subacromial corticosteroid injection for rotator cuff disease and intra-articular injection for adhesive capsulitis may be beneficial although their effect may be small and not well-maintained. There is a need for further trials investigating the efficacy of corticosteroid injections for shoulder pain. Other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
236
0
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 373 publications
(251 citation statements)
references
References 36 publications
5
236
0
10
Order By: Relevance
“…In addition, a few clinical studies have directly compared local injection of a corticosteroid with systemic NSAIDs, but the current literature does not conclusively provide evidence to support that one treatment is better than the other [42]. The Cochrane Collaboration's systematic review concluded that although there is evidence in support of corticosteroid injections, the effect may be no better than with systemic NSAIDs [42,44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few clinical studies have directly compared local injection of a corticosteroid with systemic NSAIDs, but the current literature does not conclusively provide evidence to support that one treatment is better than the other [42]. The Cochrane Collaboration's systematic review concluded that although there is evidence in support of corticosteroid injections, the effect may be no better than with systemic NSAIDs [42,44].…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Analgesic benefits of intra-articular injection of corticosteroids in rheumatoid arthritis may be more sustained (up to 3 months). 47 Drawing on these data from other parts of the musculoskeletal system, it is a reasonable hypothesis that intra-articular injection of corticosteroids could produce at least short-term pain relief in a different synovial joint that is causing pain.…”
Section: Why Might Injecting Facet Joints Be Helpful?mentioning
confidence: 99%
“…43 Ultrasound-guided steroid injection may be considered in primary/secondary adhesive capsulitis with associated degenerative osteoarthritis and articular effusion. 44 This treatment showed improvement in clinical outcome, both in terms of pain reduction and increased mobility. 45 Another possibility is to obtain a capsular distension with lidocaine and hyaluronic acid; according to Park et al, 46 this option is as effective as steroid injection in pain relief and functional improvement.…”
Section: Intra-articular Injections and Hyaluronic Supplementation Ofmentioning
confidence: 87%